Debates in allergy medicine: Specific immunotherapy in children with atopic dermatitis, the "con" view. Issue 1 (December 2016) - Ginsberg, David; Eichenfield, Lawrence
Abstract Atopic dermatitis (AD) is a common chronic skin condition in children that has a proven association with other atopic conditions and allergies. These associations, like the general pathophysiology of AD, are complex and not fully understood. While there is evidence for the efficacy of specific immunotherapy (SIT) in pediatric asthma and allergic rhinitis (AR), there is a lack of strong data to support its use in AD. IgE has been shown to be elevated in many patients with AD, but it is an unreliable biomarker due to variability and great fluctuation over time, poor positive predictive value for clinically relevant allergy, and poor correlation with disease state. In spite of this, almost all studies of SIT use either positive skin prick testing (SPT) or serum specific IgE levels to guide therapy. Allergen avoidance, with some exceptions, is generally not effective at controlling AD in children. The few studies that have investigated the efficacy of SIT in children with AD have produced conflicting results, and a lack of reproducibility with a standard treatment protocol. Limited studies have shown clinical improvement in mild to moderate AD cases, but no effect on more severe patients. Uncontrolled studies are difficult to interpret, due to the natural history of remission or "outgrowing" of AD over time in many patients without specific interventions. Drawbacks to SIT include the length of treatment, poor compliance, cost, and potential side effect profile. The potential for misdirection of time and energy away from skin directed therapy could negatively impact on AD outcomes.